Challenges for room temperature operation of electrically pumped GeSn lasers - A. R. Ellis; D. A. Duffy; I. P. Marko; S. Acharya; W. Du; S. Q-. Yu; S. J. Sweeney (Scientific Reports)
Abstract Recent demonstrations of room-temperature lasing in optically pumped GeSn show promise for future CMOS compatible lasers for Si-photonics applications. However, challenges remain for electrically pumped devices. Investigation of the processes that limit device performance is therefore vital in aiding the production of future commercial devices. In this work, a combined experimental and modelling approach is utilised to explore the dominant loss processes in current devices. By manipulating the band structure of functioning devices using high hydrostatic pressure techniques at low temperature, the dominant carrier recombination pathways are identified. This reveals that 93 $$~± ~$$ ± 5% of the threshold current is attributable to defect-related recombination at a temperature, T = 85 K. Furthermore, carrier occupation of L-valley states (carrier leakage) is responsible for 1.1 $$~± ~$$ ± 0.3% of the threshold current, but this sharply increases to 50% with a decrease of just 30 meV in the L- $$Γ$$ Γ separation energy. This indicates that thermal broadening of a similar order may reproduce these adverse effects, limiting device performance at higher temperatures. Temperature dependent calculations show that carrier occupation of indirect valley L-states strongly affects the transparency carrier density and is therefore very sensitive to the Sn composition, leading to an effective operational temperature range for given Sn compositions and strain values. Recommendations for future device designs are proposed based on band structure and growth optimisations.